Associations between gestational diabetes mellitus and the neurodevelopment of offspring from 1 month to 72 months: study protocol for a cohort study. Issue 11 (24th November 2020) - Li, Chao; Zhou, Ping; Cai, Yixi; Peng, Bin; Liu, Yongfang; Yang, Ting; Li, Yinying; Hu, Yirong; Fu, Yajun; Wang, Zhenming; Peng, Hong; Zhang, Yue; et al.
Abstract : Introduction: Gestational diabetes mellitus (GDM) is a common gestational disease and an important global public health problem. GDM may affect the short-term and long-term health of offspring, but the associations between GDM and the neurodevelopment of offspring of mothers with GDM (OGDM) are still unclear, and studies based on the Chinese population are lacking. We aim to determine the associations between GDM and the neurodevelopment of OGDM by studying a cohort of OGDM and offspring of non-GDM mothers. Methods and analysis: The single-centre prospective cohort study is being conducted in China over 7 years. A total of 490 OGDM (GDM group) and 490 fromof healthy mothers (control group) will be enrolled during the same period. Baseline characteristics, neuropsychological development scores and clinical data at specific time points (at 0, 1, 3, 6, 12, 24, 36, 48, 60 and 72 months old) will be collected from the children in both groups until the age of 6 years. The associations between GDM and the neurodevelopment of OGDM from infancy to preschool age will be analysed using a multiple linear regression model adjusted for confounders. In addition, we will compare longitudinal data to further assess the effects of GDM on neurodevelopmental trajectories. Ethics and dissemination: The study has been approved by the Ethics Committee of the Children's Hospital of Chongqing Medical University (Approval Number: (2019) Institutional Review Board (IRB) (STUDY) No. 85). The findings of this study will be disseminated through open access journals, peer-reviewed journals and scientific meetings. Trial registration number: NCT03997396 .